PERANCANGAN PENGUKURAN KINERJA KARYAWAN DI MONUMEN KAPAL SELAM SURABAYA - Jessi Suhartini Gondowijoyo; Bonnie Soeherman (CALYPTRA, 2018)
It can’t be argued that human resources are the most important in a organization. This is because his/her role as the executor of human resources even though human resources also has innate traits difficult to control. Therefore, every organization needs a control in order to create alignment goals between employees and organization.The results of the evaluation conducted in this study indicate that there are several issues related to the performance of employees who must be repaired immediately. From the results of this study, the researcher finds some existing problems related to employee performance, analyzes what causes the problem, informs the implicationsarising from the problem, and provide recommendations on the design of employee performance measurement to facilitate the organization in achieving the objectives. The main problem that occurred in the Monument Submarine related to the problem of control "No Want". This happens because some of the weaknesses of management control systems that have been running in the museum so that employees are less motivated in working.The purpose of this research is to provide the employee performance measurement designwhich is "the main key" in the organization. This research uses qualitative approach and included in applied research. The methods used are interviews with owners, employees, and tourists. In addition, also used methods of observation and document analysis to obtain accurate information.